Development of functional group tolerant and room temperature hydrogen borrowing enolate alkylation reactions - Bailey, EP (2023)
This thesis describes work completed to expand the scope of hydrogen borrowing enolate alkylation reactions. It was hypothesised that the development of a room temperature reaction would allow utility of a breadth of chemical space previously undemonstrated in these reactions at high temperatures (80–180°C). The first strategy to achieve this was via the generation of excited state intermediates of the hydrogen borrowing cycle using visible light energy and a designed catalyst. A room temperature visible light driven reaction was realised and detailed mechanistic studies unveiled the role of visible light.